The continuous increase in the number of systemic lupus erythematosus cases in Brazil in the COVID-19 era - Nelson Pereira MARQUES; Nádia Carolina Teixeira MARQUES; Edson Hilan Gomes de LUCENA; Daniella Reis Barbosa MARTELLI; Eduardo Araújo Oliveira; Hercílio MARTELLI-JUNIOR (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aims to reevaluate and compare the data from the Brazilian Unified Health System (SUS) on the number of diagnoses of systemic lupus erythematosus (SLE) in the pre-pandemic period with those in the pandemic period, as well as to compare the first year (2020) of the COVID-19 pandemic in Brazil with the last year (2021), to update the data, and to verify whether SLE disease control measures were effective in 2021. There was a consistent and significant increase in the incidence of SLE cases all over Brazil between the first and second pandemic years and between the pre-pandemic triennium and the second pandemic year. Therefore, it is inescapable to have larger clinical studies with different populations to better understand the relationship between these two conditions and find measures to improve the control of this disease.